Abdominal pseudohernia in a child after surgical correction of congenital scoliosis: case report - Nadirov, Nurbek; Vissarionov, Sergey; Khusainov, Nikita; Filippova, Alexandra; Sazonov, Vitaliy (Frontiers in Pediatrics, 2024)
Abdominal wall relaxation is a rare complication of various surgical procedures or diseases, when the intercostal or upper lumbar nerves are affected, and the innervation of the muscles of the abdominal wall is damaged. The result is a mass that can visually mimic a ventral hernia. We present a clinical case and the results of a literature review on this topic. Clinical case The 2 years 5 months patient diagnosed with a congenital deformity of the spine (posterolateral hemivertebra) underwent extraction of the hemivertebra from the retroperitoneal approach. In the postoperative period, a pseudohernial protrusion of the anterior abdominal wall was observed. 4.5 months later the protrusion resolved spontaneously. Discussion Abdominal wall relaxation is studied worldwide and is presented primarily as clinical case reports, mainly in older patients with neurological diseases. Single cases of this pathology are described among children. The Th10-Th12 roots are most often affected. Possible manifestations include: bloating and abdominal pain, pseudo-obstruction of the small and/or large intestine, and constipation. In the described case, only unilateral bloating at rest was observed, which increased with crying and strain. The natural course and prognosis of this diagnosis are usually favorable—the recovery period, according to the literature, takes an average of 4–5 months, which also coincided with our case. Conclusion Pseudohernias are a rare complication and may can occur during correction of spinal deformities in children. This condition is a transient disorder of the anterior abdominal wall muscles, the cause of which may be neuropathy caused by infection, metabolic disorders, or mechanical damage. The main principles of treatment of this condition include active observation and symptomatic therapy. The prognosis is usually favorable.